Integrasi Keimanan dan Tradisi: Analisis Peran Gereja Toraja dan Tallu Lolona dalam Harmonisasi Budaya dan Agama - Novi Krisdyanti (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This research explores the role of the Toraja Church and Tallu Lolona in integrating local traditions into religious practices. Through interviews, observations, and document analysis, we found that the Toraja Church has successfully created a harmonious model between Christian faith and Toraja cultural heritage. Tallu Lolona, as a spiritual leader, plays a central role in maintaining this balance. These findings provide deep insights into the unique dynamics between tradition and faith in the Toraja Church, with a positive impact on the spiritual and cultural life of the community.